Recent Medico-Legal Developments on the Issue of Epilepsy and Driver’s License Requirements in the Italian and European Legislation - Brenno Mazzariol; Antonella Pastorini; Alessandro di Luca; Natale Mario di Luca (Behavioural Neurology)
Epilepsy is a condition that comprises a group of neurological disorders characterized by seizures. Forms of epilepsy that produce abrupt bouts that cause lapses in consciousness may pose a major road safety problem for drivers who, while going through a seizure, could seriously harm themselves as well as others. A fundamental strategy for the purpose of reducing the risk of car accidents caused by epileptic drivers is constituted by prevention, in addition to adequate pharmacological therapies. In that respect, forensic medicine plays a pivotal role, since it deals with the set of requirements that must be met by those who have been diagnosed with epilepsy in order to get a driver’s license, and with the obligation to signal such individuals to the national Driver and Vehicle Licensing Agency (in Italian: Motorizzazione Civile). In that regard, the Italian legislative framework is partly hazy in some respects, which the authors have set out to analyze herein, taking into account recently issued European norms. The aim of this paper was to better understand the current Italian legislation in the matter of epilepsy and driver’s license requirements, especially regarding the medical criteria that must be met in order to obtain the driving license. The importance of those criteria is underlined by the fact that they directly influence (and are influenced by) the safety for the drivers and for the persons involved in car accidents. Thus, we can consider the issue not only strictly of medico-legal relevance but also from the standpoint of primary prevention. The analysis was conducted by reviewing the most recent documents of medico-legal relevance, in the light of European Union legislation. The authors have ultimately stressed the need for clearer and straightforward regulations, given that professional liability may arise whenever a driver’s license is issued, in disregard of legal norms, to an individual who then causes a road accident.